Ecovillages and felling/thinking education: Knowledge and popular education in the Vraja Dhama Ecovillage from Hare Krishna Movement - Santos, Otávio Augusto Chaves Rubino dos (2021)
This research speaks about a felling/thinking education in knowledge and practices of popular education present in the community Hare Krishna called Ecovillage Vraja Dhama, located in the rural area of Caruaru - PE. The object of study is the knowledge and pedagogical practices woven by its residents in Ecovillage, field in which popular education takes place, understanding that it takes place on a concrete floor. As methodology, we serve the bibliographic review and the participant observation. As categories of analysis we use “Ecovillages”, “Popular Education” and “Education and the Hare Krishna Movement”. In the results, we emphasize that it is important to broaden our vision so that we can perceive and experience other knowledge. This knowledge generates a strangeness of the look and, therefore, other practices of feeling. It is a way of decolonizing the patriarchal, dualistic, oppressive and vertical gaze in the production of knowledge and, thus, perceiving other gazes in a construction and experience of a felling/thinking education.